Homelessness in Latin America (2013-2023): Perspectives and Interventions - Romero-Plana, Virginia (Prospectiva. Revista de Trabajo Social e Intervención Social, 2026)
Homelessness is a complex phenomenon arising from the convergence of three factors: low income, lack of human development and social exclusion. This study analyses scientific articles on homelessness in Latin America based on a systematic review of literature from five databases from 2013 to 2023. In terms of output, the subject has received limited coverage, despite growing interest since 2017. The focus remains largely economic and class-based without incorporating a gender perspective, a critical approach to neoliberalism and patriarchy, or an intersectional analysis. The care system for the homeless is based on the need-resource model, emphasising the welfare-based approach that remains prevalent in social work. Four areas of intervention related to multidimensional poverty stand out: basic care, housing, occupational therapy, and harm reduction.